Analisis Proses Penagihan Piutang atas Transaksi Angkutan Non-Semen “Terpal” PT Semen Indonesia Logistik - Kholifatun Nur Handini; Vicky Vendy (Forum Kerjasama Pendidikan Tinggi, 2026)
This study was conducted to analyze the procedures for accounts receivable collection and the handling of problematic receivables in the Non-Cement “Tarpaulin” transportation services at PT Semen Indonesia Logistik (SILOG), as well as to examine the obstacles that may hinder the receivables collection process within the company. The research adopts a case study method with a qualitative approach. Data collection techniques used in this study include interviews with three relevant informants, direct observations, and documentation analysis. The findings reveal that the receivables collection process begins with the delivery of billing documents, including invoices and supporting documents, and ends with the settlement of receivables through the SAP system. Receivables that become due are classified into four aging categories: 60 days, 120 days, 180 days, and 365 days. The collection of overdue receivables is carried out through communication via WhatsApp and, in some cases, direct visits to customers. Common obstacles encountered in the receivables collection process include difficulties in coordinating with customers, receivables that are difficult to collect due to customer insolvency or bankruptcy, and unidentifiable receivables or incoming payments. This research is expected to help the company evaluate its current receivables collection procedures more comprehensively. By identifying potential problems early, the company can make necessary improvements and develop more effective strategies for managing the receivables collection process